Optimized boron fusion with magnetic trapping by laser driven plasma block initiation at nonlinear forced driven ultrahigh acceleration. (6th June 2014) - Lalousis, P.; Hora, H.; Moustaizis, S.
Abstract Fusion reactions of solid density boron-11 with protons after initiation of a fusion flame by very powerful picosecond laser pulses were derived for plane geometry. The problem of lateral energy losses with laser beams was solved by using spherical geometry, where however the gains are limited. The other elimination of losses now available by cylinder-axis symmetric 10 kilotesla magnetic fields is possible needing laser powers in the exawatt range. Estimations are presented by varying parameters for reducing the necessary laser pulse powers to lower values by up to a factor 100.